High-intensity interval exercise training before abdominal aortic aneurysm repair (HIT-AAA): protocol for a randomised controlled feasibility trial. Issue 1 (10th January 2014) - Tew, Garry A; Weston, Matthew; Kothmann, Elke; Batterham, Alan M; Gray, Joanne; Kerr, Karen; Martin, Denis; Nawaz, Shah; Yates, David; Danjoux, Gerard
Abstract : Introduction: In patients with large abdominal aortic aneurysm (AAA), open surgical or endovascular aneurysm repair procedures are often used to minimise the risk of aneurysm-related rupture and death; however, aneurysm repair itself carries a high risk. Low cardiopulmonary fitness is associated with an increased risk of early post-operative complications and death following elective AAA repair. Therefore, fitness should be enhanced before aneurysm repair. High-intensity interval exercise training (HIT) is a potent, time-efficient strategy for enhancing cardiopulmonary fitness. Here, we describe a feasibility study for a definitive trial of a pre-operative HIT intervention to improve post-operative outcomes in patients undergoing elective AAA repair. Methods and analysis: A minimum of 50 patients awaiting elective repair of a 5.5–7.0 cm infrarenal AAA will be allocated by minimisation to HIT or usual care control in a 1:1 ratio. The patients allocated to HIT will complete three hospital-based exercise sessions per week, for 4 weeks. Each session will include 2 or 4 min of high-intensity stationary cycling followed by the same duration of easy cycling or passive recovery, repeated until a total of 16 min of high-intensity exercise is accumulated. Outcomes to be assessed before randomisation and 24–48 h before aneurysm repair include cardiopulmonary fitness, maximum AAA diameter and health-related quality of life. In the post-operative period, we will record destination (ward or critical care unit), organ-specific morbidity, mortality and the durations of critical care and hospital stay. Twelve weeks after the discharge, participants will be interviewed to reassess quality of life and determine post-discharge healthcare utilisation. The costs associated with the exercise intervention and healthcare utilisation will be calculated. Ethics and dissemination: Ethics approval was secured through Sunderland Research Ethics Committee. The findings of the trial will be disseminated through peer-reviewed journals, and national and international presentations. Trial registration: Current Controlled Trials ISRCTN09433624 .